Pemanfaatan Media Gambar Pada Materi Pengenalan Huruf Hijaiyah Untuk Santri Usia Dini di Lembaga Pendidikan Qur’an Nurul Hidayah Desa Donosari Kecamatan Sruweng - Listiana Utami; Devi Yaniar Wi Hargina (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2026)
This research aims to (1) find out how to use image media in hijaiyah letter material for early age students at LPQ Nurul Hidayah, Donosari village. (2) To find out the advantages and disadvantages of using image media. This research is a type of research carried out, namely field research which ultimately results in a report in qualitative descriptive form. Meanwhile, the object of the research is how to implement the use of image media in hijaiyah letter material for early age students at LPQ Nurul Hidayah, Donosari village. Meanwhile, the research subjects were ustadz, ustadzah and students of LPQ Nurul Hidayah of Donosari Village. To obtain the information and data needed for research, researchers used several methods, namely observation, interviews and documentation. In analyzing the data obtained from the research results, the author uses data reduction analysis techniques, data presentation, and drawing conclusions. The results of the research obtained: (1) Utilization of image media in hijaiyah letter material for early age students at LPQ Nurul Hidayah Donosari village. In learning to recognize hijaiyah letters using image media, the ustadzah carried out three series of processes to carry out the learning, namely planning, implementation and evaluation.(2) The advantages and disadvantages of using image media in hijaiyah letter material for early age students at LPQ Nurul Hidayah Donosari village, the advantages are, increasing the enthusiasm and enthusiasm of the students in learning, making it easier for the students to remember the shape of the hijaiyah letters, and increasing the students' creativity in learning. coloring hijaiyah letters. Apart from that, there are also several disadvantages of using image media, namely: firstly, choosing learning media requires the teacher's astuteness to adapt it to learning needs, secondly it only emphasizes eye sense perception, thirdly the image size is limited.